Redundancies at North Sydney Ferry Terminal - George, Roy (Relations industrielles / Industrial Relations, 1966)
In 1968, following technical change at the North Sydney Ferry Terminal, the working force needed will be 100 men instead of 800 working regularly and 200 on a part time basis. In this article, the author analyses the human problems arising from a technological change and the solutions brought forward by a committee.